Evidence for Significant Skew and Low Heritability of Competitive Male Mating Success in the Yellow Fever Mosquito Aedes aegypti - Claudia A. S. Wyer; Vladimir Trajanovikj; Brian Hollis; Alongkot Ponlawat; Lauren J. Cator (Evolutionary Applications)
ABSTRACT Aedes aegpyti mosquitoes are vectors of several viruses of major public health importance, and many new control strategies target mating behaviour. Mating in this species occurs in swarms characterised by male scramble competition and female choice. These mating swarms have a male‐biased operational sex ratio, which is expected to generate intense competition among males for mating opportunities. However, it is not known what proportion of swarming males successfully mate with females, how many females each male is able to mate with, and to what extent any variation in the male mating success phenotype can be explained by genetic variation. Here, we describe a novel assay to quantify individual male mating success in the presence of operational sex ratios characteristic of Ae. aegypti. Our results demonstrate that male mating success is skewed. Most males do not mate despite multiple opportunities, and very few males mate with multiple females. We compared measures of male mating success between fathers and sons and between full siblings to estimate the heritability of the trait in the narrow h 2 and broad H 2 sense, respectively. We found significant broad sense heritability estimates but little evidence for additive genetic effects, suggesting a role for dominance or epistatic effects and/or larval rearing environment in male mating success. These findings enhance our understanding of sexual selection in this species and have important implications for mass‐release programmes that rely on the release of competitive males.